2022
DOI: 10.1159/000524146
|View full text |Cite
|
Sign up to set email alerts
|

Huntington’s Disease Progression and Caregiver Burden

Abstract: Huntington’s disease (HD) is a neurodegenerative, progressive disorder conditioned by a mutation in the <i>HTT</i> gene. Its progression is dependent on the causative mutation extension. Caregivers of individuals affected by HD, most often patients’ relatives, are burdened with the care. This study aims to assess the caregivers’ burden cross-sectionally and longitudinally and look for biological and clinical patients-related burdening factors. In total, 144 caregiver-patient pairs observed annually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…By carefully reviewing the literature and our data, we found that the caregiver burden of HD patients in Korea was high, which was consistent with previous reports in other countries. [9][10][11][12][13]15 The present study provides useful insight into the factors associated with the caregiver burden in Korea. Previous studies have shown that advanced disease and low functional capacity were associated with the caregiver burden.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…By carefully reviewing the literature and our data, we found that the caregiver burden of HD patients in Korea was high, which was consistent with previous reports in other countries. [9][10][11][12][13]15 The present study provides useful insight into the factors associated with the caregiver burden in Korea. Previous studies have shown that advanced disease and low functional capacity were associated with the caregiver burden.…”
Section: Discussionmentioning
confidence: 84%
“…The present study provides useful insight into the factors associated with the caregiver burden in Korea. Previous studies have shown that advanced disease and low functional capacity were associated with the caregiver burden [ 9 , 10 , 12 ]. It makes sense that as patients’ function declines, their dependency on caregivers increases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While several previous studies on the experiences of caregivers, namely parents, of CRDs have been conducted in Poland, including Huntington disease [32][33][34] or Prader-Willi syndrome 35 , most often they focuses either on the challenges and needs related to caring for such a child, caregivers' burden or social functioning of a family whose member experiences RD. However, few data are available on the experiences of CRD caregivers with the healthcare system in Poland 20 .…”
Section: Discussionmentioning
confidence: 99%